2019
DOI: 10.3390/aerospace6040039
|View full text |Cite
|
Sign up to set email alerts
|

Axial Ratio and Gain Enhancement of a Circular-Ring Slot Antenna Using a Pair of Asymmetrical Rectangular Slots and a Parasitic Patch for a Radio Beacon on a Nanosatellite

Abstract: Radio beacons enable measurements of ionospheric radio scintillations and total electron content (TEC). These beacons transmit unmodulated, phase-coherent waves in S-band frequencies. Many satellite applications require circularly polarized (CP) wideband antennas. Their compact size, lightweight, and simple fabrication method make CP antennas suitable for small satellite systems. The slot antenna has wideband impedance, but the 3 dB axial ratio bandwidth (ARBW) is narrower compared to the impedance bandwidth (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Given the target L-band frequency (1-2 GHz), the ARBW of the proposed antenna scheme (77.87%) was significantly wider than that of [13,15] (19.86% and 36.87%, respectively). In comparison with [16,[22][23][24], for C-and S-band applications (30.8-72.9%), the proposed antenna scheme could achieve a wider ARBW (77.87%). Table 4.…”
Section: Resultsmentioning
confidence: 97%
“…Given the target L-band frequency (1-2 GHz), the ARBW of the proposed antenna scheme (77.87%) was significantly wider than that of [13,15] (19.86% and 36.87%, respectively). In comparison with [16,[22][23][24], for C-and S-band applications (30.8-72.9%), the proposed antenna scheme could achieve a wider ARBW (77.87%). Table 4.…”
Section: Resultsmentioning
confidence: 97%
“…Wide-beam CP radiation is a feature of the projected antenna that makes it desirable for RF energy harvesting applications. In another research paper, a circularly slotted antenna is presented in [29], and the design is shown in Figure 2(c). This research aimed to develop a design for enhancing a circularly slotted antenna's CP performance in order to achieve wide 3-dB axial ratio bandwidth and a higher gain at 2.4 GHz.…”
Section: Circularly Polarized Sub-6 Ghz Antennasmentioning
confidence: 99%
“…A qualitative comparison between the proposed equilateral CPW-fed slot antenna and six S-band antenna designs with metasurface [20][21][22][23][24][25][26][27][28][29][30][31] is now provided; refer to Figure 25. We analyze, compare, and evaluate the suitability of all these antenna designs for 3U CubeSats using the following criteria: small physical size at S-band, wide impedance and Axial Ratio bandwidth, low reflection coefficient (<−10 dB), orientability, and high gain at S-band.…”
Section: Comparative Study: Brief Comparison With Literature Workmentioning
confidence: 99%